Youth engagement in sweetpotato production and agribusiness: the case of Northern Uganda - Mdege, Norita; Mayanja, Sarah; Mudege, Netsayi Noris (Routledge, 2022)
Abstract Using qualitative data collected in Gulu and Omoro districts, Northern Uganda, this paper discusses factors influencing youth engagement in sweetpotato production and agribusiness in a post-conflict environment. The purpose is to understand the factors in order to promote young people’s participation in sweetpotato and other agricultural value chains. Thirteen young women and eleven young men were interviewed in individual in-depth interviews. Additionally, 74 young women and 85 young men participated in 16 sex-disaggregated focus group discussions. Our study identifies that rural youth’s participation in sweetpotato production and agribusiness is a product of the intersection of broader community/national context, individual circumstances (age, gender, marital status, education and social class), and individual and collective agency. Our proposed strategies to encourage youth participation in the agricultural value chain consider young people’s intersectional identities and address national- and community-level issues such as access to knowledge and information, land, markets and gendered power hierarchies.
Keywords: Young men, young women, agricultural value chain, small-scale farming, post-conflict, Sub-Saharan Africa